2008
DOI: 10.1523/jneurosci.4126-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Tlx1 and Tlx3 Coordinate Specification of Dorsal Horn Pain-Modulatory Peptidergic Neurons

Abstract: The dorsal spinal cord synthesizes a variety of neuropeptides that modulate the transmission of nociceptive sensory information. Here, we used genetic fate mapping to show that Tlx3 ϩ spinal cord neurons and their derivatives represent a heterogeneous population of neurons, marked by partially overlapping expression of a set of neuropeptide genes, including those encoding the anti-opioid peptide cholecystokinin, pronociceptive Substance P (SP), Neurokinin B, and a late wave of somatostatin. Mutations of Tlx3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(120 citation statements)
references
References 51 publications
7
113
0
Order By: Relevance
“…Furthermore, whether other transmitter receptor genes in general are controlled by Tlx1/3 or Ptf1a is unknown. Previous studies have also characterized the transcriptional regulation of peptides in glutamatergic and GABAergic neurons (Bröhl et al, 2008;Huang et al, 2008;Xu et al, 2008). In this study, we have further shown that two genes encoding additional peptides, adenylate cyclase activating polypeptide 1 (PACAP/Adcyap1) and neurotensin (NT), are controlled by Tlx1/3.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, whether other transmitter receptor genes in general are controlled by Tlx1/3 or Ptf1a is unknown. Previous studies have also characterized the transcriptional regulation of peptides in glutamatergic and GABAergic neurons (Bröhl et al, 2008;Huang et al, 2008;Xu et al, 2008). In this study, we have further shown that two genes encoding additional peptides, adenylate cyclase activating polypeptide 1 (PACAP/Adcyap1) and neurotensin (NT), are controlled by Tlx1/3.…”
Section: Introductionmentioning
confidence: 55%
“…Another transcription factor Ptf1a acts to suppress Tlx3 expression and promote GABAergic differentiation (Glasgow et al, 2005;Mizuguchi et al, 2006;Hori et al, 2008). Three studies including ours have also shown that the transcription factors that determine the glutamatergic or GABAergic cell fate also control the expression of distinct sets of peptides in the dorsal horn selectively (Bröhl et al, 2008;Huang et al, 2008;Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 57%
“…؊/؊ embryos We have demonstrated previously that transcription factors Tlx1 and Tlx3 specify the glutamatergic cell fate and control a set of downstream targets including transcription factors, peptides, and transmitter receptors in the dorsal horn (Qian et al, 2002;Cheng et al, 2004;Cheng et al, 2005;Xu et al, 2008) (data not shown). The specific expression patterns of MafA and c-Maf prompted us to investigate whether MafA and c-Maf were involved in a transcriptional cascade to control the expression of some target genes of Tlx1 and Tlx3 in the developing dorsal spinal cord.…”
Section: Developmental Defects In Spinal Dorsal Horn Of C-mafmentioning
confidence: 91%
“…The generation of Tlx1, Tlx3, Lbx1, and Tlx3-cre mutant mice has been described previously (Roberts et al, 1994;Gross et al, 2000;Shirasawa et al, 2000;Xu et al, 2008). Ptf1a cre mutant mice, which have Cre-recombinase in place of the Ptf1a protein-coding region, were kindly donated by Dr. Christopher Wright (Vanderbilt University, Nashville, TN) and obtained from the Mutant Mouse Regional Resource Centers (MMRRC) (Kawaguchi et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…For example, cAMP response element binding protein (CREB) was originally described as a cAMP-dependent transcriptional stimulator for somatostatin (2). Furthermore, transcriptional networks specify peptidergic neurons in Drosophila and mammals (e.g., [3][4][5][6][7][8][9]. Finally, accumulation of amidated neuropeptides and DCVs in Drosophila neurons is enhanced by the transcription factor Dimmed (DIMM) (10)(11)(12)(13).…”
mentioning
confidence: 99%